Characterization of Thermo- and Detergent Stable Antigenic Glycosylated Cysteine Protease of Euphorbia nivulia Buch.-Ham. and Evaluation of Its Ecofriendly Applications - Shamkant B. Badgujar; Raghunath T. Mahajan (The Scientific World Journal)
An antigenic glycosylated cysteine protease has been purified from the latex of Euphorbia nivulia Buch.-Ham. It exhibits remarkable protease activity in the presence of metal ions, oxidizing agents, organic solvents, and detergents. This enzyme showed potential role in leather processing industry due to its dehairing activity for animal hide without hydrolyzing fibrous proteins, producing, by this way, a better quality product. The enzyme can also be used for silver recovering from X-ray plates. In addition, the stability (temperature and surfactants) and hydrolysis of blood stain data also revealed its application in detergent industries. Agriculturally, this protease finds application in biocontrol process against the infectious management of root knot nematode, Meloidogyne incognita. Biologically, it shows noticeable wound healing, haemostatic and antibacterial activity.